The Commercial Determinants of Nonalcoholic Beer: Redemption, Revenue, or Men’s Harm Reduction? - John L. Oliffe; Nina Gao; Mary T. Kelly; Trevor Goodyear; Murray Drummond; Christine Levesque; Katherine White (American Journal of Men's Health)
Public awareness about the connections between men’s alcohol use and poor health outcomes, including increased male suicide risk, has led to reduced consumption and increased use of nonalcoholic beverages—most prominently nonalcoholic beer (NAB). Marketed as a healthy substitution option (i.e., periodically switching to an NAB rather than abstaining from alcoholic beer), the rapidly growing NAB sector might be somewhat redemptive, wherein the alcoholic beer industry (as the predominant producers of NAB) is selling harm reduction to men, albeit for profit. The commercial determinants of NAB are, however, complex and have significant implications for legislation and policy. For example, in Canada, NAB is exempt from alcoholic beer excise duty but considered beer for the goods and services and harmonized sales taxes. Coupled with industry production costs and profit margins, these taxes contribute to NAB and alcoholic beer retail price parity. From a public health perspective, there are also concerns about increasing alcoholic beer brand recognition and sales revenue by extending NAB visibility in more places (e.g., supermarkets), contexts (e.g., taking medication), and activities (e.g., driving). The current article highlights (1) the connections between men’s alcohol use and health risks, ahead of discussing, (2) the rise of NAB, and mapping (3) NAB legislation and policy implications. We conclude with a discussion about the redemption, revenue, and men’s harm reduction potentials, pragmatically arguing the need to both regulate and incentivize NAB. Proposed are promising directions for future research with the goal of reducing men’s alcohol use and associated harms.